(untitled) (Great Neck, N.Y., 1956)
This is book introduction dawn and the morning star, toward a common cause, the ideal and the fact, the rise of the common man, the blue and the gray, darwin and politics, from McKinley to Wilson, the modern era.
Keywords: United States,Hoa Kỳ; History,Lịch sử